US inflation and inflation uncertainty over 200 years. (2nd July 2018) - Bredin, Don; Fountas, Stilianos
Abstract : This article uses historical US inflation data covering over two centuries to examine the impact of the establishment of the US Federal Reserve on average US inflation and inflation uncertainty. We find that the founding of the Fed is associated with higher average US inflation and lower inflation uncertainty. Critically, these results are not driven by the post-1980 period, where the Fed policy is characterised by the dual mandate. Other important results are that the gold standard period is associated with both lower inflation and inflation uncertainty, and that banking and stock market crises are a positive determinant of inflation uncertainty and perhaps inflation. World Wars I and II and the US Civil War are associated with both higher inflation and higher inflation uncertainty. In addition, we find that the central bank has responded to increasing inflation uncertainty in a stabilising manner in support of the Holland hypothesis.